Atrial fibrillation pattern, left atrial diameter and risk of cardiovascular events and mortality. A prospective multicenter cohort study. Issue 3 (9th November 2020) - Menichelli, Danilo; Sciacqua, Angela; Cangemi, Roberto; Andreozzi, Paola; Del Sole, Francesco; Violi, Francesco; Pignatelli, Pasquale; Pastori, Daniele; ,
Abstract: Background: There are conflicting evidence on the association between atrial fibrillation (AF) pattern, such as persistent/permanent (Pers/Perm) and paroxysmal (PAF) AF and risk of ischemic events. We investigated if left atrial diameter (LAd) may affect the risk of cardiovascular outcomes according to AF pattern. Methods: Prospective multicenter observational including 1, 252 non‐valvular AF patients (533 PAF and 719 Pers/Perm AF). Study endpoints were cardiovascular events (CVEs), major adverse cardiac events (MACE) and CV death. LA anteroposterior diameter (LAd) was obtained by transthoracic echocardiography. Results: Pers/Perm AF patients had a higher proportion of LAd above median than PAF (≥44 mm, 59.5% vs 37.5% respectively, P  < .001). In a mean follow‐up of 42.2 ± 31.0 months (4, 315 patients/year) 179 CVEs (incidence rate [IR] 4.2%/year), 133 MACE (IR 3.1%/year), and 97 CV deaths (IR 2.2%/year) occurred. Compared to patients with LAd below median, those with LAd above the median had a higher rate of CVEs (log‐rank test, P  < .001), MACE (log‐rank test P  < .001), and CV death (log‐rank test P  < .001). Multivariable Cox regression analysis showed that LAd above the median was associated with CVEs, (HR 1.569, 95% CI 1.129‐2.180, P  = .007) MACE (HR 1.858, 95% CI 1.257‐2.745, P  = .002) and CV death (HR 2.106, 95% CI 1.308‐3.390, P  = .002). The association between LAd and outcomes was evident both in PAF and Pers/Perm AF patients. No association between AF pattern and outcomes was found. Conclusion: LAd is a simple parameter that can be obtained in virtually all AF patients and can provide prognostic information on the risk of CVEs, MACE and CV death regardless of AF pattern.